Measurement of LoRa signal propagation in urban areas utilizing aerial gateway and ground gateway - Wenxin Tang; Honggang Zhao; Sitong Chen; Aoyang Li; Wenjing Yang; Wei Cheng; Yong Li; Limeng Dong (Scientific Data)
Abstract LoRaWAN, as a leading technology of LPWAN, has become a crucial driver of smart cities. Meanwhile, drones have become a key tool for enhancing LoRaWAN network performance. In this study, a comprehensive measurement of a large-scale LoRaWAN network in an urban environment was conducted. Specifically, 28 LoRaWAN end-devices have been deployed in various locations, covering outdoor, indoor, and multiple floors of buildings. Moreover, an aerial gateway mounted on the DJI Mavic 3, along with three ground gateways, has been deployed for data collection. The performance of aerial gateway at altitudes of 50 m, 100 m, and 150 m was also tested. Finally, a total of 28,576 raw data entries were obtained, including valuable information like RSSI, SNR, and timestamps. A preliminary evaluation of the LoRaWAN network was conducted to validate the dataset. To the best of our knowledge, this dataset is the first publicly available UAV-assisted LoRaWAN network measurement data in an urban environment. We believe that our dataset can be utilized in various research areas, including channel modeling, localization, and deep learning.